The development of a real time, interactive water level monitoring system through SMS with AC load control - Buhion, Jordan; Buhion, Judelyn; Ocon, Janice (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Flooding and water level rise is a constant problem Filipinos encounter every year. The Philippines has a reasonably well-defined rainy season due to the monsoons. To counter the adverse effects of this potentially disastrous phenomenon, modern flood monitoring and forecasting systems are indispensable. Thus, the utilization of a comprehensive GSM-based system for monitoring water level of streams, lakes, rivers and other bodies of water in areas prone to flooding is essential to effectively increase the people’s awareness in real time. The system works by receiving water level update queries through text messaging from any cellphone number and texts back the accurate water level (in feet and inches) based on the actual reading from the system’s sensor. The water level update can be done “on demand” or every 10 minutes. The system can analyze the water level patterns such as the rate of water level rising or receding and includes its observation on the SMS to be sent. It also has integrated anti-theft features such as intruder sensor and alarm and the system locator through GPS (Global Positioning System). They are designed to protect the system against thieves and intruders. The system is also capable of controlling an AC (Alternating Current) load. This allows the system to be used in various applications that require water monitoring and automatic control. It can control AC loads of up to 2000 watts. The control function can be “automatic” or through SMS (Short Message Service) depending on the application.